2016
DOI: 10.3389/fphar.2016.00402
|View full text |Cite|
|
Sign up to set email alerts
|

Safety Profiles of Tripterygium wilfordii Hook F: A Systematic Review and Meta-Analysis

Abstract: Objective: Tripterygium wilfordii Hook F (TwHF) is a widely used and effective treatment for inflammatory diseases. There have been concerns about its toxicity but no adequate synthesis of the evidence for adverse events (AEs). We aimed to undertake a clinically informative, systematic safety profile of TwHF.Methods: We undertook a systematic review and meta-analysis of experimental studies and observational studies. We searched electronic databases and conference abstracts. Safety outcomes were rates of commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…112 However, its consumption may have potential side effects such as adverse reproductive outcomes, kidney and liver damage, cardiac damage, skin and hair disorders, weight change and even death, thus, is not recommended in countries like UK and USA. 113115…”
Section: Alternative Medicinesmentioning
confidence: 99%
“…112 However, its consumption may have potential side effects such as adverse reproductive outcomes, kidney and liver damage, cardiac damage, skin and hair disorders, weight change and even death, thus, is not recommended in countries like UK and USA. 113115…”
Section: Alternative Medicinesmentioning
confidence: 99%
“…Furthermore, tripterygium glycoside tablets lead to acute hepatic injury, myocardial damage, and gastrointestinal inflammatory changes [18,19]. Tripterygium glycoside tablets and its preparations also have obvious gastrointestinal toxicity, mainly manifested as nausea, diarrhea, and liver impairment [9]. Clinical studies have confirmed that tripterygium glycoside tablets can affect a variety of metabolic pathways, including lipid metabolism, tricarboxylic acid cycle, digestion, and absorption [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Both the therapeutic and toxic effects of tripterygium glycoside tablets are mediated by the same mechanisms that induce apoptosis, oxidative stress, and the release of lactate dehydrogenase [8]. A metaanalysis conducted by Chi Zhang et al showed that the main side effects of tripterygium glycoside tablets were gastrointestinal symptoms (13.3%), adverse reproductive outcomes (11.7%), skin reactions (7.8%), and hematological and cardiovascular events (6.5%) [9]. Some studies have shown that liver damage caused by tripterygium glycoside tablets has a dose-dependent relationship [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, searching on CMap with gene expression data from tissues (liver and hypothalamus) showing diminished ER stress and improved leptin/insulin receptor signaling as query signatures successfully identified celastrol as an effective leptin sensitizer and chemical chaperone ameliorating obesity in the leptin-resistant mouse model [145]. Celastrol is a phytochemical originally extracted from the root of the thunder god vine, Tripterygium wilfordii , which has been used as a medicinal plant in China and other East Asian countries as a treatment of inflammatory diseases such as rheumatoid arthritis [145,146]. Furthermore, using the gene expression signature of celastrol as a query on CMap uncovered that withaferin A is also a chemical chaperone and a leptin sensitizer, and significantly ameliorates obesity [147].…”
Section: Connectivity Map (Cmap)mentioning
confidence: 99%